2018
DOI: 10.1180/clm.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Direct Orange 34 dye fixation by modified kaolin

Abstract: The present study investigated the adsorption behaviour of Direct Orange 34, a highly toxic dye used in textile industries in Tunisia, on modified kaolinite-rich clays. A kaolin from the Sidi Bader (SDB) area was activated with hydrochloric acid to create the activated clay referred to hearafter as SDBa, or treated with FeSO4•7H2O to obtain its Fe-saturated form, Fe-SDB. The adsorbents were characterized by X-ray diffraction, X-ray fluorescence, transmission electron microscopy, BET surface area and zeta-poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
(101 reference statements)
2
4
0
Order By: Relevance
“…This model is in good agreement with other MB adsorption on clay reported in recent articles. These values of q e are close to those reported by Andolssi (2016) and Chargui et al (2018) in their studies on the kinetics of MB adsorption by clay.…”
Section: Equilibrium and Kinetics Of Mb Adsorptionsupporting
confidence: 91%
See 1 more Smart Citation
“…This model is in good agreement with other MB adsorption on clay reported in recent articles. These values of q e are close to those reported by Andolssi (2016) and Chargui et al (2018) in their studies on the kinetics of MB adsorption by clay.…”
Section: Equilibrium and Kinetics Of Mb Adsorptionsupporting
confidence: 91%
“…Clays have been studied for various applications such as adsorption and catalysis (Chaari et al 2008;Hajjaji et al 2013;Hajjaji et al 2016;Mhammedi and Benguella 2016). Clayey mineral was some of natural materials that were successfully used for contaminant removal (Chargui et al 2018). This approach of natural adsorbents for the treatment of wastewater was the focus of much research in the last decade (Ben Amor et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The meteoric fluids associated with this recent weathering event affected the whole district. They are most likely responsible for the numerous weathering profiles observed in the area, including in the superficial part of the Albian-Priabonian marls and in the Numidian Flysch Formation, which hosts kaolinitic industrial clays [3,6,7].…”
Section: Stratigraphic Frame Of the Nefza-sejnane Districtmentioning
confidence: 99%
“…The mining district of Nefza-Sejnane contains numerous ores and raw material deposits, including the Zn-Pb mineralization of Sidi Driss, the vertebrate-bearing Douahria basin that hosts a SEDEX deposit [1], the halloysite-bearing iron deposit of Tamra Formation [2][3][4][5], the Fe-LREE-U enriched breccia of Oued Belif [5], and kaolinitic clays of the late Oligocene Numidian Flysch Formation [6,7]; (Figures 1 and 2). From the Miocene onwards, these deposits experienced successive circulations of Fe-rich fluids of mixed meteoric and hydrothermal origins.…”
Section: Introductionmentioning
confidence: 99%
“…The hysteresis loop could be observed, due to capillary condensation (Chai et al, 2020;Thommes et al, 2015). The modification of kaolin through high temperature and acid-alkali treatment improved the surface area of the material from 11.31 to 16.23 m 2 /g due to the formation of mesopores (Chargui et al, 2018;Shu et al, 2014). A previous study showed similar results whereby the acid treatment of kaolin improved its surface area from 10.44 to 19.27 m 2 /g (Chai et al, 2020).…”
Section: Morphology Functional Groups Of Cqd and Surface Areamentioning
confidence: 58%